Analisis Tendensi Mahasiswa terhadap Media Pembelajaran Online pada Mata Kuliah Bahasa Inggris di Masa Pandemi Covid-19 - Nawa, Agus Trioni (Tapis: Jurnal Penelitian Ilmiah, 2021)
The spread of Covid-19 has not ended, it requires restrictions interaction between humans to minimize its transmission. This condition presents a new face of education – online learning. State Islamic Institute of Metro as one of the educational institutions, facilitates a website-based platform called the Learning Management system (LMS) in accommodating this worry. However, there are still many obstacles, including the limited internet quota, poor internet network connection, and lack of student focus in attending the learning process. Departing from these problems, lecturers are required to be more creative and innovative in delivering learning subjects by considering the students' needs and tendencies towards the online learning media provided. This study involved 191 respondents to delve information about most required learning media during the Covid-19 pandemic. The interview and online questionnaires were employed in collecting data. The study revealed that there were three most required learning media in the English learning process; video learning, written text materials, and virtual learning.